Fostering Ethnomathematics in Projective Geometry: A Hypnoteaching Framework for Effective Distance Learning - Jafaruddin, Jafaruddin; Chen, Wen-Haw (SEAMEO Regional Centre for QITEP in Mathematics, 2023)
This study evaluated the impact of integrating students' cultural backgrounds into online learning to improve understanding and participation. It employed